2005
DOI: 10.1016/j.jtcvs.2004.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic prophylaxis for postoperative atrial tachyarrhythmia in general thoracic surgery: Evidence from randomized clinical trials

Abstract: Calcium-channel blockers and beta-blockers are effective in reducing postoperative atrial tachyarrhythmia. The use of these medications should be individualized, and possible adverse events of beta-blockers should be taken into account. Randomized clinical trials do not support the use of digitalis in general thoracic surgery. The value of magnesium as a supplement to a main prophylactic regimen should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 40 publications
0
32
0
2
Order By: Relevance
“…Management of fluid balance and electrolyte levels can decrease the incidence of atrial fibrillation. Multiple medications including β-blockers, calcium-channel blockers, amiodarone and digoxin have been used as prophylaxis against the development of atrial fibrillation [33]. Riber et al completed a meta-analysis and found amiodarone and magnesium sulfate to be the most effective and safest drugs as prophylaxis against postoperative atrial fibrillation [34].…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Management of fluid balance and electrolyte levels can decrease the incidence of atrial fibrillation. Multiple medications including β-blockers, calcium-channel blockers, amiodarone and digoxin have been used as prophylaxis against the development of atrial fibrillation [33]. Riber et al completed a meta-analysis and found amiodarone and magnesium sulfate to be the most effective and safest drugs as prophylaxis against postoperative atrial fibrillation [34].…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Neither class of medication reduces mortality. 122 In patients with postoperative supraventricular tachycardia unresponsive to adenosine, esmolol appears to be better than diltiazem for rapid conversion to sinus rhythm. 125 Digitalis may precipitate atrial fibrillation, and data on other medications are limited.…”
Section: Postoperative Arrhythmiasmentioning
confidence: 99%
“…48,121 Increased intravascular volume, whether iatrogenic or resulting from primary cardiac dysfunction, is a common contributing factor. Supraventricular tachycardias are more common after thoracic surgery, occurring in Ն15% cases, 122 than other types of noncardiac surgery; risk factors include a faster preoperative heart rate and older age. 123 Nonsustained ventricular tachycardia is not independently associated with a worse prognosis and need not be treated.…”
Section: Postoperative Arrhythmiasmentioning
confidence: 99%
“…O efeito da amiodarona não é significativo, e o digital produz dano, aumentando o risco absoluto (ARA) desse evento em 10,4% (NNH: 9) 1 . Apesar da estimativa de benefício, a ocorrência de eventos adversos foi avaliada apenas com o uso de bloqueadores de cálcio e de ß-bloqueadores, havendo ARA de hipotensão em 6,7% (NNH:15) e 22,9% (NNH:4), e de bradicardia em 6,2% (NNH:16) e 20,4% (NNH:5), respectivamente.…”
unclassified
“…O Termo de Consentimento Livre e Esclarecido (TCLE), exigido nos estudos envolvendo seres humanos, é em sua essência expressão de autodeterminação (direitos) do ser humano, derivado do respeito ao referencial bioético da autonomia 1 . Assinar o TCLE representa a anuência do sujeito em participar do estudo.…”
unclassified